Genetic and Segregation Analysis of Escherichia coli Strains Containing a Tandem Duplication of the trpD-purB Region of the Chromosome - Simonian, Michael H. (1978)
Genetic and segregation analysis of Escherichia coli strains containing a partial duplication of the trp operon reveal that the 2.5-min-long region trpD-purB is duplicated in tandem in the chromosome. The adjacent loci cysB and fabD are not duplicated. Although one copy of the duplicated region is longer than the maximum size of bacteriophage P1kc transducing fragments, the frequency at which the duplicated segment trpDCBA is transferred by transduction to tonB-trp deletion strains is equal to that observed for transfer of the normal trp operon. This suggests that three-point recombination events believed to account for transduction of long duplications occur as frequently as two-point recombination events believed to account for normal transduction. Cotransduction frequencies of trpDCBA with the duplicated loci tonB, galU, tyrT, and hemA are very similar to those for the trp operon with the same loci. This indicates that normal genetic linkage is maintained during the three-point recombination event. However, purB, which is normally unlinked to trp by transduction, is closely linked to trpDCBA and thus must be near the repeat point of the duplication. Transduction tests with point mutations in the trp operon indicated that the repeat point occurs near the normal boundary between trpE and trpD. Segregation analysis of heterogenotes constructed from tonB-trp deletion strains shows that the frequency at which a marker is lost is approximately proportional to its distance from the repeat point. This finding is consistent with a random, singlesite crossover event during segregation. Several observations indicate that non-reciprocal genetic exchange also occurs between copies of the duplication. Analysis of heterogenotes containing dadR1 and dadR(+) demonstrate that the mutant allele is transdominant.